Problems of legal regulation of activity of Department of Internal Affairs on safety of the personality: some theoretical and practical questions. (Journal of actual problems of jurisprudence, 2016)
This article finds out theoretical and practical problems of legal regulation of activity of the Department of Internal Affairs on safety of the personality reveal. The author of article believes that the concept the personality is key in the right and reflects the main characteristics of the person as legal entity. Also this article describes the concept of safety of the personality reveals. The conclusion is drawn that one of the main objectives of the state is to create favorable conditions for normal, full activity of the personality. The author of article draws a conclusion that at the heart of human rights is an idea of certain level of human dignitywhich can’t be restrained or limited neither by government, nor the certain person. In the article the conclusion was done, that radical approach is necessary to reforms in law enforcement agencies of the RoK. In the conclusion the certain recommendations were offered on observation of the right of the personality, on safety and on strengthening of a mode of legality in activity of law-enforcement bodies of the RoK.
Keywords: personality; human rights; safety; law enforcement agencies; state; jurisprudence; police; law-enforcement bodies